2016
DOI: 10.1111/jep.12674
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of medication errors related to sliding scale insulin by the introduction of a standardized order sheet

Abstract: Insulin is frequently used for glycemic control. Medication errors related to insulin are a common problem for medical institutions. Here, we prepared a standardized sliding scale insulin (SSI) order sheet and assessed the effect of its introduction. Observations before and after the introduction of the standardized SSI template were conducted at Gifu University Hospital. The incidence of medication errors, hyperglycemia, and hypoglycemia related to SSI were obtained from the electronic medical records. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
(12 reference statements)
2
9
0
Order By: Relevance
“…Several studies have reported the efficacy of the use of physician‐approved protocols by pharmacists in pharmaceutical care . Further, the introduction of standardised protocols has also been useful for preventing medication errors . The present study clearly demonstrates that implementation of protocol‐based management based on co‐operation between physicians and pharmacists that consists of checking the criteria for administration of anticancer drugs was useful for reducing anticancer drug wastage after preparation.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Several studies have reported the efficacy of the use of physician‐approved protocols by pharmacists in pharmaceutical care . Further, the introduction of standardised protocols has also been useful for preventing medication errors . The present study clearly demonstrates that implementation of protocol‐based management based on co‐operation between physicians and pharmacists that consists of checking the criteria for administration of anticancer drugs was useful for reducing anticancer drug wastage after preparation.…”
Section: Discussionsupporting
confidence: 54%
“…[11][12][13] Further, the introduction of standardised protocols has also been useful for preventing medication errors. 14,15 The present study clearly demonstrates that implementation of protocol-based management based on co-operation between physicians and pharmacists that consists of checking the criteria for administration of anticancer drugs was useful for reducing anticancer drug wastage after preparation. After introducing the present measure, pharmacists implemented a total of 100 interventions by checking each criterion for administration of anticancer drugs based on the protocol prior to preparation of anticancer drugs.…”
Section: F I G U R E 3 Comparison Of the Percentage (A) And Cost (B) mentioning
confidence: 56%
“…Tingle (2012) has reported that many adverse outcomes experienced by people with diabetes are associated with sub-optimal inpatient care. Reports that insulin is one of the most likely prescribed drug to cause harm to patients is supported by evidence from Europe (Rayman, 2010;Tingle, 2012), Asia (Harada et al, 2016), Australia (NSW Health, 2015) and America (NICE-SUGAR Study Investigators, 2012;Pennsylvania Patient Safety Authority, 2010;Rayman, 2010), with data suggesting that 33% of reported insulin errors have resulted in death (Rayman, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A large and growing body of literature has investigated the root causes of medication administration errors and proposed strategies of reducing these errors accordingly [2][3][4]. However, giving the fact that insulin medication errors occurred more often than any other type or class of drug [5,6], and can cause detrimental or even irreversible damages to patients [7], so far, there has been little discussion about how to reduce insulin administration errors in inpatients from a nursing perspective. The purpose of this paper is to examine the prevalence, consequences, and contributing factors of insulin administration errors world widely from a nursing perspective.…”
Section: Introductionmentioning
confidence: 99%